2016
DOI: 10.1515/danb-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Qualification Requirements for Foreign Suppliers in Public Procurement – Evidence from the Czech Republic

Abstract: Qualification requirements for foreign suppliers in Public Procurement (PP) are quite different in each European Union (EU) member state. The most complex requirements for foreign suppliers in the context of public purchases are included in the Czech PP law. The aim of this paper is to make an overview of the problem of qualification requirements for foreign suppliers in the PP law of the CR. Its sub-objectives are the identification and explanation of solutions to the problem in the PP legislation of neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The importance of the institutional settings for the proper functioning of the public procurement market is emphasized by Pavel and Sičáková-Beblavá (2008). The analysis of the public procurement legal regulation (former one) was carried out by Vyklický et al (2016), who showed that potential foreign suppliers were facing unnecessary administrative burdens, which ultimately discourage the submission of tenders from "foreign" EU countries. A study of the current legal regulations has been missing so far.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the institutional settings for the proper functioning of the public procurement market is emphasized by Pavel and Sičáková-Beblavá (2008). The analysis of the public procurement legal regulation (former one) was carried out by Vyklický et al (2016), who showed that potential foreign suppliers were facing unnecessary administrative burdens, which ultimately discourage the submission of tenders from "foreign" EU countries. A study of the current legal regulations has been missing so far.…”
Section: Introductionmentioning
confidence: 99%